Development of a decision aid for children faced with the decision to undergo dental treatment with sedation or general anaesthesia. Issue 5 (29th September 2016) - Hulin, Joe; Baker, Sarah R.; Marshman, Zoe; Albadri, Sondos; Rodd, Helen D.
Abstract : Background: Decision aids are tools used to help individuals faced with difficult healthcare decisions. They help patients further understand the treatment options available and encourage the sharing of information between patients and clinicians. Aim: To develop a decision aid for young patients faced with the decision to undergo dental treatment with inhalation sedation, intravenous sedation, or general anaesthesia (GA). Design: Qualitative interviews with dental patients (aged 10–16 years), and their parents/guardians were used to inform the content of a draft decision aid. Following further revisions, a pilot evaluation of the decision aid was conducted. Patients referred for dental treatment with sedation or GA were recruited from a UK dental hospital. Patients ( n = 15) and parents/guardians ( n = 13) assigned to the intervention group received the decision aid and routine clinical counselling, whereas patients ( n = 17) and parents/guardians ( n = 13) in the control group only received routine clinical counselling. Participants completed measures of knowledge, decisional conflict, and dental anxiety. Results: Knowledge scores were significantly higher for participants who received the decision aid when compared to standard care. There were no other significant differences between groups. Conclusions: A decision aid was successfully developed, and initial findings suggest such tools could be beneficial to dental sedation or GA patients and their parents/guardians. Further research is required on the use of such tools in primary care settings, with particular attention to the impact of the decision aid on attendance and completion rates of treatment.